Viral proteins and RNAs in BHK cells persistently infected by lymphocytic choriomeningitis virus. - van der Zeijst, B A (1983)
Some Syrian hamster cell lines persistently infected with lymphocytic choriomeningitis virus (LCMV) do not produce extracellular virus particles but do contain intracytoplasmic infectious material. The proteins of these cells were labeled with [35S]methionine or with [3H]glucosamine and [3H]mannose, and immunoprecipitates were prepared with anti-LCMV sera. A substantial amount of the LCMV nucleocapsid protein (molecular weight about 58,000) was detected, along with GP-C, the precursor of the virion glycoproteins GP-1 and GP-2. GP-1 and GP-2 themselves were not detected. A new method of transferring proteins electrophoretically from sodium dodecyl sulfate-polyacrylamide gels to diazotized paper in high yield revealed several additional LCMV proteins present specifically in the persistently infected cells, at apparent molecular weights (X10(3] of 112, 107, 103, 89, 71 (probably GP-C), 58 (nucleocapsid protein), 42 to 47 (probably GP-1), and 40 (possibly GP-2). By iodinating intact cells with I3, GP-1 but not GP-2 or GP-C was revealed on the surfaces of the persistently infected cells, whereas both GP-1 and GP-C were found on the surfaces of acutely infected cells. The absence of GP-C from the plasma membrane of the persistently infected cells might be related to defective maturation of the virus in these cells. Cytoplasmic viral nucleoprotein complexes were labeled with [3H]uridine in the presence or absence of actinomycin D, purified partially by sedimentation in D2O-sucrose gradients, and adsorbed to fixed Staphylococus aureus cells in the presence of anti-LCMV immunoglobulin G. Several discrete species of viral RNA were released from the immune complexes with sodium dodecyl sulfate. Some were appreciably smaller than the 31S and 23S species of standard LCMV virions, indicating that defective interfering viral RNAs are probably present in the persistently infected cells. Ribosomal 28S and 18S RNAs, labeled only in the absence of actinomycin D, were coprecipitated with anti-LCMV serum but not with control serum, indicating their association with LCMV nucleoproteins in the cells.